Does hedging make economic sense for American Airlines? - Vieira, Bruno Lucio (2014)
This study evaluates the impact of hedging in company value by analyzing how American Airline consolidated group’s market value is impacted by changes in the level of next year’s fuel needs hedged and total value of its outstanding agreements from 1989 to 2010. A descriptive and qualitative research methodology was used. Secondary data was collected for a case study.The results indicate that it makes economic sense to hedge fuel costs. However, investors have negatively valued increases in hedge positions.